Chordoma: an assessment of future treatment and management strategies - Uhl, Matthias; Debus, Jürgen (Expert Opinion on Orphan Drugs, 2014)
Introduction: Chordomas are locally aggressive, rare bone tumors that develop from remnants of the notochord. Most of the experience in the past years has arisen from single centers with low patient numbers. This review gives an overview of current standards in diagnosis, therapy and recent research. Areas covered: After a brief explanation of pathogenesis, clinical manifestations and diagnosis of chordoma, the current treatment options, including surgery, radiotherapy and systemic therapy are presented. The comprehensive literature search was performed until November 2013 by using PubMed. Only peer-reviewed published articles were used. Due to the rarity of the disease, smaller case series were also considered. Expert opinion: The therapy for chordoma should be performed in prospective randomized trials. The development of new treatment concepts requires translational research in a network of expert centers. The transcription regulator factor, brachyury, is currently the most promising approach for understanding and targeting chordoma in the future. For faster clinical advancement, the development of more cellular and animal models is necessary.
Gesehen am 14.08.2020